A fallible narrator and an inscrutable object: desire as structure in Dostoevsky’s The Eternal Husband - Phillips, James (Studies in East European thought, 2025)
This article argues that one of the means by which Dostoevsky achieves polyphony in the limited point-of-view narration of The Eternal Husband (1870) is through the tension between the character Velchaninov’s overt aversion and his subterranean attraction to Trusotsky, the cuckold of the title. While Trusotsky is more forthright in expressing his love for Velchaninov and has thus previously raised the question of homosexuality for commentators on Dostoevsky’s novella, the text also provides sufficient clues to infer that Velchaninov is erotically responsive. The subtlety of Dostoevsky’s depiction of this responsiveness is crucial to the polyphonic effect he secures for the work. The narration, which proceeds from Velchaninov’s perspective, imbricates the discrete layers of what is thought, what is said and what is done without being openly thought. The monological principle of composition, to which the limited point-of-view narrative format generically predisposes many earlier writers but whose alienness to Dostoevsky is Bakhtin’s central contention, thereby fails to assert itself in the novella.